E-Evaluation in Ethnomathematics-Based Learning with the Gasing Method to Improve Numerical Literacy and Metacognitive Abilities - Ni Komang Diah Eka Parwati; I Made Suarjana; I Nyoman Laba Jayanta (Universitas Pendidikan Ganesha, 2024)
The problem that occurs in mathematics learning in grade V is the low metacognitive ability and numerical literacy of students. This happens because the evaluation given is still limited to memorizing formulas alone. This study aims to analyze the effectiveness of ethnomathematics-based e-evaluation to improve students' numerical literacy and metacognitive abilities. The research model used is the ADDIE development model (analyze, design, development, implementation, evaluation). The subjects of this study were 35 grade V students. The data collection method used in this study was a questionnaire and test. The data collection instrument in this study will use a rating scale and a short essay test. The data analysis technique used is quantitative descriptive and inferential statistics. Based on the t-test table on the metacognitive ability variable, it was found that the significance value (2-tailed) was 0.000. These results indicate that the significance value is less than 0.05 (significance level 5%) or p <0.05. This means that H0 is rejected and H1 is accepted. Then in the numerical literacy variable, it was found that the significance value (2-tailed) was 0.000. These results indicate that the significance value is less than 0.05 (significance level 5%) or p <0.05. This means that H0 is rejected and H1 is accepted. Based on these results, it can be concluded that ethnomathematics-based e-evaluation can be used in mathematics learning because it is effective in improving students' metacognitive and literacy abilities.